Operative Standards for Cancer Surgery : Volume 1, Section 4: Colon /: Volume 1, Section 4: Colon. (2019) - Program, American College of Surgeons Clinical Research; Oncology, Alliance for Clinical Trials in; Nelson, Heidi D; Hunt, Kelly K
No abstract available